Sistematis Literatur Review (SLR) : Peningkatan Kapasitas dan Pengelola Sumber Daya dalam Usaha Mikro, Kecil dan Menengah pada Badan Usaha Milik Desa - Hambali Hanafia; Irzami Hawa; Katarina Rika Apriliana; Iriyanti Iriyanti; Agus Munandar (Journal on Education, 2023)
The purpose of this study is to analyze capacity building and resource management in micro, small and medium enterprises, village-owned enterprises, namely in the field of human resource development and training in several villages by providing ongoing assistance and collaborating with various parties. The study used a systematic literature review approach through several stages, namely identifying research questions, establishing a data base for research results, selecting relevant research results and indexing data extraction, synthesizing results using narrative methods and presenting data. Methodology This research was conducted with a search engine (Google Chrome) using the address https://scholar.google.com/ chosen according to the address of the largest open database website that can be accessed by many parties who search with the search term "UMKM BUMDES. PDFs”. From the results of a literature review search found 31 articles with topics related to MSMEs using BUMDes then the results of the analysis show that creative industry synergy is needed, this synergy requires a support system, namely the state, universities, the media and the business world. state support is very important in this case then the university can help with concept development and further assistance the mass media is a means of publication and village products then the community can become successful and the company can become a productive partner in the village. Then it is then managed by several regions in Indonesia starting from planning to controlling BUMDes so that it continues to run well then it is regulated in regulations and based on the approved articles of association. As for how to start a business such as services and trade as well as BUMDes management can be done digitally so that management can function optimally.